Angiotensin-converting enzyme (ACE) I/D polymorphism is a risk factor of allergic rhinitis - Li, P.; Cao, L.; Han, X. (Cellular and Molecular Biology, 2017)
Some previous studies and meta-analysis investigated the association between ACE I/D polymorphism and allergic rhinitis risk. However, the results were conflicting. This meta-analysis, therefore, was performed to evaluate the association between ACE I/D polymorphism and allergic rhinitis risk. Online electronic databases (PubMed and EMBASE) were searched. The strength was evaluated by calculating the OR and 95% CI. Five studies were finally included in this meta-analysis. These studies included 681 cases and 629 controls. ACE I/D polymorphism was significantly associated with allergic rhinitis risk (OR = 1.17; 95% CI 1.07 – 1.29; P = 0.001). In the subgroup analysis of race, Asians showed the increased allergic rhinitis risk (OR = 1.15; 95% CI 1.02 – 1.30; P = 0.03). In a stratified analysis by age, adults with ACE I/D polymorphism showed the increased allergic rhinitis risk (OR = 1.16; 95% CI 1.04 – 1.29; P = 0.006). However, children did not have the significantly increased allergic rhinitis risk (OR = 1.24; 95% CI 0.99 – 1.56; P = 0.06). In conclusion, this meta-analysis indicated that ACE I/D polymorphism was significantly associated with allergic rhinitis risk.